„MEMORIA METRULUI”, UN MOD DE FUNCȚIONARE A „MEMORIEI CULTURALE”. HEXAMETRUL ÎN CULTURA ROMÂNEASCĂ - Paladian, Cristinia (The Romanian Cultural Institute, 2023)
This article is dedicated to the study of hexameter in the Romanian cultural memory. It is observed that no poetic form appears in isolation; it is either taken over or reshaped from already existing meters, which is a common mode of operation within the mechanism of historical and cultural succession and a way in which the text reads history and aligns itself with it. A significant example in this regard is the presence of an antique metrical-quantitative hexameter in the Romanian cultural memory, representing the relationship between cultures. The reception of hexameteris a model of ingenious imitation of the ancient form, as well as a model of creative interpretation from a national perspective. Prosodic investigations conducted demonstrate that in the Romanian cultural memory, the hexameter is a skillful imitation of the three forms of antique meter. It is a syllabo-tonic equivalent of the “canonical”metrical-quantitative form, typically conveyed through dactylo-trochees, but each model carries the specific imprint of the creative poet. Thus, in Romanian literature, we distinguish several forms of hexameter. a). The dactylo-trohaic hexameter, which is a variation of the antique hexameter with intensity accents on the first and fourth feet, as in the imitations found in classical German poetry. b) The dactylic hexameter, which is characteristic of the primary rhythm of Greek versification. c) “Neohexameters” or derivatives of the hexameter are dactylo-trochaic variants of the Latin form with intensity accents on the fourth feet (occasionally on the third feet), but they allow deviations from the antique canons at the rhyme level. d) “Pseudo-hexameters” are original forms with significant deviations from the canonical norms of antique versification. The diverse reception of the hexameter illustrates the creative and innovative capacity of Romanian poets in prosody. The examples analyzed represent a reinterpretation of the cultural traditions of antiquity while simultaneously reproducing the expressive significance of the ancient meter.
"MEMORY OF THE METER", A MODE OF OPERATION OF "CULTURAL MEMORY". THE HEXAMETER IN ROMANIAN CULTURE
Keywords: memory of the meter; cultural memory; hexameter; dactylo-trochaic hexameter; pseudo-hexameter; neohexameter